NILAI TAMBAH (VALUE ADDED) OLAHAN PRODUK ABON IKAN LELE UNTUK PENINGKATAN PENDAPATAN MASYARAKAT DESA PENEN KECAMATAN SIBIRU-BIRU KABUBATEN DELI SERDANG SUMUT - Dian Hendrawan; Mhd. Nuh; Dedi Kusbiantoro; Yenni Asbur; Suliyenman Syahputra (Jurnal Pengabdian Mitra Masyarakat, 2022)
The community service carried out is located in Penen Village, sub-district. Sibiru-Biru, Deli Serdang Regency, North Sumatra Province. This community service aims to improve the knowledge and skills of the community through counseling and assistance in processing and managing shredded catfish as well as creating real business opportunities in Penen village in the future. That the added value generated from the processing of shredded catfish is Rp. 32,000 per kilogram. The share of labor in the shredded processing agroindustry is 21.28%. The profit earned is IDR 47,000/Kg with a profit rate of 46.81%.